ANALISIS DAN DESAIN SISTEM APLIKASI KANTIN ELEKTRONIK (E-CANTEEN) BAGI MAHASISWA DAN STAFF UNIVERSITAS - Cahyani, Putri Rigita; Maylinasari, Lely; Ambami, Sinta Aisyah; Putra, Bagaskara Rahadi (Journal of Digital Business and Innovation Management, 2023)
The E-Canteen application is an innovative solution that aims to change the traditional way of managing canteens into a more efficient and practical process through digital technology. This application allows students and staff to order food online via mobile devices or computers. In managing traditional canteens, there are often long queues and a waste of time in ordering food. In addition, sometimes, there is a mismatch between the available food stock and the user's wishes. The E-Canteen application is here to solve these problems by providing efficient and practical solutions.